2021
DOI: 10.1002/brb3.2059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short‐term cognitive‐coping therapy on resting‐state brain function in obsessive‐compulsive disorder

Abstract: Background Obsessive‐compulsive disorder (OCD) tends to be treatment refractory. Recently, cognitive‐coping therapy (CCT) for OCD is reported to be an efficacious psychotherapy. However, the underlying neurophysiological mechanism remains unknown. Here, the effects of CCT on OCD and the resting‐state brain function were investigated. Methods Fifty‐nine OCD patients underwent CCT, pharmacotherapy plus CCT (pCCT), or pharmacotherapy. Before and after a 4‐week treatment, Yale‐Brown obsessive‐compulsive scale (Y‐B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
(70 reference statements)
1
5
0
Order By: Relevance
“…In previous rs-fMRI studies, researchers observed a lower centrality degree of the lingual gyrus [56,57], and the ALFF values were found to be increased in the insular cortex but decreased in the lingual gyrus of OCD patients, which was associated with symptom severity [41,58]. These abnormal local activity patterns could be normalized by coping through cognitive therapy [59]. Interestingly, we further observed that there was a trend of correlation between the reduced intrinsic connectivity of the right insula and lingual gyrus and the enhanced severity of depressive symptoms rather than OCD-related symptoms in the OCD group.…”
Section: Hypoconnectivity Of the Right Insula And Lingual Gyrusmentioning
confidence: 87%
See 1 more Smart Citation
“…In previous rs-fMRI studies, researchers observed a lower centrality degree of the lingual gyrus [56,57], and the ALFF values were found to be increased in the insular cortex but decreased in the lingual gyrus of OCD patients, which was associated with symptom severity [41,58]. These abnormal local activity patterns could be normalized by coping through cognitive therapy [59]. Interestingly, we further observed that there was a trend of correlation between the reduced intrinsic connectivity of the right insula and lingual gyrus and the enhanced severity of depressive symptoms rather than OCD-related symptoms in the OCD group.…”
Section: Hypoconnectivity Of the Right Insula And Lingual Gyrusmentioning
confidence: 87%
“…In previous rs-fMRI studies, researchers observed a lower centrality degree of the lingual gyrus [ 56 , 57 ], and the ALFF values were found to be increased in the insular cortex but decreased in the lingual gyrus of OCD patients, which was associated with symptom severity [ 41 , 58 ]. These abnormal local activity patterns could be normalized by coping through cognitive therapy [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increment of the resting motor threshold of the right hemisphere after repetitive transcranial magnetic stimulation (rTMS) treatment was associated with a reduction of OC symptoms ( Mantovani et al, 2006 ). Ma et al (2021) scanned OC disorder patients with resting-state functional magnetic resonance (rs-fMRI) before and after cognitive-coping therapy. The increase of resting state activity (i.e., spontaneous neural activity) in the right hemisphere after cognitive-coping therapy was associated with the reduction of OC symptoms severity.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most studies of RT in older adults have not been conducted in healthy older adults, but rather focused on those with anxiety disorders, obsessive-compulsive disorder (Ma et al, 2021; Schiepek et al, 2013), post-traumatic stress disorder (Beauregard, 2014; Karlsson, 2011), or major depression (Won Jeon & Kim, 2015; Wu et al, 2020; Dichter et al, 2010). From this prior work, we would hypothesize that RT will be associated with improved well-being, as well as decreased depression and anxiety scores.…”
Section: Introductionmentioning
confidence: 99%